Miconazole-Urea in a Buccal Film as a New Trend for Treatment of Resistant Mouth Fungal White Patches - Mady, Omar Y.; Donia, Ahmed M.; Al-Madboly, Lamiaa A. (Frontiers in Microbiology, 2018)
A growing concern about Candida albicans is the emergence of high incidence of resistance against antifungal agents, which requires searching for new medications or improving the response to the existing members. The objective of this work was to evaluate the effectiveness of the miconazole in the absence and presence of urea, as a penetration enhancer, against C. albicans. In addition to, formulating both of them in a polymer film to be used topically for treatment of mouth fungal white patches caused by C. albicans. A synergistic effect was recorded between this imidazole and urea against the test strain. Miconazole MIC (32 mg/L) was dramatically reduced to 0.0625 mg/L following combination with urea. Transmission electron microscopy explained the mechanisms of action mediated by the test agents. Minimal fungicidal dose of miconazole combined with urea showed early apoptotic cells with condensed chromatin and small blebs. Cytoplasmic leakage and necrosis in some cells was observed at high fungicidal dose. Buccal bioadhesive films were prepared using increasing values of the drug MIC and urea. The physicochemical characters of the prepared films including; film weight, thickness, swelling index, drug content, folding endurance, surface pH, bioadhesion force and time and drug release kinetics, were studied. Microbiological evaluation of all prepared films showed an increase in the inhibition zone diameters for films containing increasing concentrations of both miconazolae and urea in a concentration-dependent manner (30-40 mm) compared to miconazole alone (18 mm). Based on our results, the prepared films are promising for buccal administration of miconazole/urea showing synergistic effect for treatment of C. albicans infection.